COMPARAÇÃO ENTRE A APLICAÇÃO ÚNICA E FRACIONADA DO LASER DE BAIXA INTENSIDADE NA MOVIMENTAÇÃO DENTÁRIA EM RATOS - Nicodemos, Valéria Rezende (2012)
Low-level laser (LLL) has proved its biostimulators effects in orthodontic movement, increasing the cell response and, reducing the treatment time. However, would the use of LLL be more effective with more power in a short time (single irradiation), or both low power and time in fractioned applications? The aim of this study was to compare the movement of 64 rats molars, and their histological changes under orthodontic force, released from a NiTi closed coil (20gf). The animals were divided into 4 groups (each group with 16 rats), according to the following protocols of laser GaAlAs(780nm): control group, under orthodontic movement, with no laser irradiation; Total 1 Group, orthodontic movement associated to a single laser application (P=60mW/DE=15J/cm2/Et=6J/t=100sec), on day zero; Total 2 Group, with laser irradiation on day zero, under the protocol (P=20mW/DE=15J/cm2/E=6J/t=300sec); and fractioned group, with LLL irradiation on days 0,3 and 7, using the protocol (P=20mW/DE=5J/cm2/E=2J/t=100sec). The animals were sacrificed in 4 moments (days 1,4,8 and 15), with four rats per group, sacrificed per day. The amount of orthodontic movement was measured in loco , with a digital caliper, before the coils were activated and, immediately after the animals sacrifice. For the histological exam, the upper jaws were removed, prepared and coloured by the H/E system. The Analysis of Variance and Tukey test were performed (p<0,05). The fractioned group revealed the greatest tooth movement, compared to the other groups (on days 4 and 8). The total 1 and 2 groups presented a greater orthodontic movement compared to control group, only on day 8, without significant statistically difference between them. This study has shown that the low-level laser accelerated the orthodontic movement, emphasizing the fractioned irradiation over the single ones.